Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1002/ece3.1890
|View full text |Cite
|
Sign up to set email alerts
|

Comparative phylogeography and evolutionary history of schizothoracine fishes in the Changtang Plateau and their implications for the lake level and Pleistocene climate fluctuations

Abstract: The water level oscillation of endorheic lakes and extent change of glaciers associated with the Asian monsoon are known as prominent representatives of climatic and environmental events in the Tibetan Plateau during the Quaternary. However, details process in spatial and temporal changes are still debated. We use the schizothoracines as a palaeoclimatic proxy to test two hypotheses concerning the evolution of Quaternary glaciations and lakes of the Changtang Plateau: (1) the Tibetan glaciations generally tend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 74 publications
0
11
0
Order By: Relevance
“…A similar demographic history was also suggested by He et al . 33 . The SDM also demonstrated that while most suitable habitats disappeared on the Qiangtang Plateau during the LGM, the Siling Co area showed a certain degree of suitability for those five taxa to live (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…A similar demographic history was also suggested by He et al . 33 . The SDM also demonstrated that while most suitable habitats disappeared on the Qiangtang Plateau during the LGM, the Siling Co area showed a certain degree of suitability for those five taxa to live (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Population genetics has experienced an increasing interest in quantifying shared and idiosyncratic attributes across demographic histories from multiple independent taxa to address questions regarding wide‐scale biogeographic, ecological and evolutionary responses to climate and landscape changes, an endeavour commonly referred as comparative phylogeography (Arbogast & Kenagy, ; Avise, ; Hewitt, , ; Hickerson et al., ; Papadopoulou & Knowles, ; Taberlet, Fumagalli, Wust‐Saucy, & Cosson, ). These comparative studies can be especially informative about how key environmental and organismal features (Carnaval, Hickerson, Haddad, Rodrigues, & Moritz, ; Carstens, Gruenstaeudl, & Reid, ; Fouquet et al., ; He et al., ; Kautt, Machado‐Schiaffino, & Meyer, ; Luo et al., ; Nadachowska‐Brzyska, Li, Smeds, Zhang, & Ellegren, ; Papadopoulou & Knowles, ; Qu et al., ; Rougemont et al., ; Smith et al., ; Stone et al., ; Wood et al., ) and selective forces (Boyko et al., ; Frantz et al., ; Gignoux, Henn, & Mountain, ; Hohenlohe et al., ; Poh, Domingues, Hoekstra, & Jensen, ; Rougeux, Bernatchez, & Gagnaire, ) affect patterns of shared and idiosyncratic histories. One approach in such investigations is to exploit multi‐taxa genetic data for comparative demographic inference under a hierarchical model, whereby hyperparameters govern the variability of a certain demographic parameter across taxa, while all other nuisance demographic parameters freely vary per each taxon (Beaumont, ; Hickerson, Dolman, & Moritz, ).…”
Section: Introductionmentioning
confidence: 99%
“…from Nam Co and the surrounding lakes, compared with more distant parts of the TP (He et al, 2016). In contrast, due to a vector-mediated passive dispersal across large areas, other aquatic taxa such as freshwater snails seem to be less influenced by drainage histories (Oheimb et al, 2011).…”
Section: Geodiversity and Evolution Of Biodiversitymentioning
confidence: 93%
“…In general, the ecoregion can serve as a proxy for community-and species-level biodiversity, which best describe communities of mammals, birds and plants (Smith et al, 2018). The TP forms a distinctive zoographical region, characterized by fauna that is adapted to high altitudes, drought, low temperatures and low oxygen levels (He et al, 2016). Certainly, the TP harbors also many unique lineages of other organisms, with higher endemism of low dispersal species (Yang et al, 2009;Clewing et al, 2016).…”
Section: Geodiversity and Evolution Of Biodiversitymentioning
confidence: 99%